Understanding dental pulp inflammation: from signaling to structure - Pohl, Sandra; Akamp, Tobias; Smeda, Martyna; Uderhardt, Stefan; Besold, David; Krastl, Gabriel; Galler, Kerstin M.; Buchalla, Wolfgang; Widbiller, Matthias (Frontiers in Immunology, 2024)
The pulp is a unique tissue within each tooth that is susceptible to painful inflammation, known as pulpitis, triggered by microbial invasion from carious lesions or trauma that affect many individuals. The host response involves complex immunological processes for pathogen defense and dentin apposition at the site of infection. The interplay of signaling between the immune and non-immune cells via cytokines, chemokines, neuropeptides, proteases, and reactive nitrogen and oxygen species leads to tissue reactions and structural changes in the pulp that escalate beyond a certain threshold to irreversible tissue damage. If left untreated, the inflammation, which is initially localized, can progress to pulpal necrosis, requiring root canal treatment and adversely affecting the prognosis of the tooth. To preserve pulp vitality and dental health, a deeper understanding of the molecular and cellular mechanisms of pulpitis is imperative. In particular, elucidating the links between signaling pathways, clinical symptoms, and spatiotemporal spread is essential to develop novel therapeutic strategies and push the boundaries of vital pulp therapy.